Investigation of Avoidable Losses Due to Effect of Pod Borer, Helicoverpa armigera (Hubner) in Chickpea - Y. A. Shinde; O. P. Veda (Cutting-edge Research in Agricultural Sciences Vol. 3, 2020)
The aim of this research is the calculate losses due to major pest of chickpea viz. pod borer, Helicoverpa armigera. Chickpea is one of the important pulse crop. Considering the economic value of this crop, protective measures need to be taken well in advance to prevent the pod damage due to pod borer. An experiment was conducted during rabi season 2009-10 at Experimental Field of Department of Entomology, Live Stock Farm, Adhartal, JNKVV, Jabalpur (M.P.), India. This study adopted in two treatment and untreated plots having equal dimensions. Chickpea variety, JG-130 was selected and planted for the study. All recommended package of practices were followed during sowing. The results were revealed that, Pod borer is notorious pest of chickpea found in Jabalpur, Madhya Pradesh and avoidable loss due to this pest on chickpea was estimated 63.64%. Gram pod borer was observed to be the major pest of chickpea which reduced the yield considerably.